1997
DOI: 10.1063/1.118590
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties and microstructures of Pt/Ba0.5Sr0.5TiO3/SrRuO3 capacitors

Abstract: A positive temperature coefficient of resistivity effect from a paraelectric Pt/(Ba 0.5 ,Sr 0.5 )TiO 3 /IrO 2 thin-film capacitor Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The reduction of SrRuO 3 to elemental Ru by Si is believed to be the most favourable candidate reaction leading to the unstable contact of SrRuO 3 with Si. Other ruthenates such as CaRuO 3 and BaRuO 3 would be expected to be unstable when in contact with Si owing to the inherent instability of the constituent binary oxide, RuO 2 . For the ternary or multicomponent oxide to be stable in contact with Si, an initial requirement must be satisfied, disregarding the potential reaction involving ternary or multicomponent products: the binary constituents must be compatible individually with the Si surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of SrRuO 3 to elemental Ru by Si is believed to be the most favourable candidate reaction leading to the unstable contact of SrRuO 3 with Si. Other ruthenates such as CaRuO 3 and BaRuO 3 would be expected to be unstable when in contact with Si owing to the inherent instability of the constituent binary oxide, RuO 2 . For the ternary or multicomponent oxide to be stable in contact with Si, an initial requirement must be satisfied, disregarding the potential reaction involving ternary or multicomponent products: the binary constituents must be compatible individually with the Si surface.…”
Section: Discussionmentioning
confidence: 99%
“…2 -5 When grown at temperatures of >500°C, an SrRuO 3 film is polycrystalline in nature with columnar morphology and metallic conductivity. 4,5 It has been observed that the interface between Si and SrRuO 3 films is susceptible to chemical reaction during the growth of SrRuO 3 , resulting in a randomly oriented polycrystalline SrRuO 3 3 an amorphous SiO 2 layer (¾3.1 nm thick) and Sr-Ru-Si polycrystalline oxides (¾5.6 nm thick). We investigated the compositional and structural characteristics of the reaction layers more precisely and concluded that the reaction layers consist of more than two layers.…”
Section: Introductionmentioning
confidence: 98%
“…In the past years, ferroelectric barium strontium titanate (Ba 1Àx Sr x )TiO 3 has been investigated extensively for application in dynamic random access memory (DRAM) and tunable microwave devices, due to its high relative dielectric constant, low dielectric loss, and strong tunability under an external electric field [1][2]. In order to obtain high performance of (Ba 1Àx Sr x )TiO 3 film, the bottom electrode layer must have high metallic conductivity, sufficient resistance to oxidation, a smooth surface, and good adhesion to the film.…”
Section: Introductionmentioning
confidence: 99%
“…CSD method is one of the methods to create/develop thin films [2][3][4][5][6][7][8][9][10][11][12], which has advantages including the ability to control the film stoichiometry with good quality, easy procedure, require relatively low cost, and generate a good crystalline phase [13][14][15]. In addition, thin films can also be fabricated by other methods such as metal organic chemical vapor deposition (MOCVD) [16][17][18], chemical vapor deposition [19], sol-gel [20][21][22][23], atomic layer deposition (ALD) [24], metal organic decomposition (MOD) [25], pulsed laser ablation deposition (PLAD) [26,27], and RF sputtering [2,21,28].…”
Section: Introductionmentioning
confidence: 99%